Winemaking performance: whether the crisis is over. Issue 5 (25th April 2019) - Goncharuk, Anatoliy G.
Abstract : Purpose: The purpose of this paper is to find how much the efficiency of winemaking has changed since the crisis of 2008 and what are the main determinants of winemaking performance in the recent decade. Design/methodology/approach: This study applied a three-stage approach to explore productivity, efficiency and profitability changes. At the first stage of the empirical study, the Malmquist Total Factor Productivity indexes based on the data envelopment analysis are used to reveal tendencies of wineries' productivity and the reasons for its changes. At the second stage, productivity indexes were used to find out the main exogenous and endogenous factors. At the final stage, the profitability change after the crisis in the context of the wine types and a size of wineries is explored. Findings: The main trends and factors of winemaking performance after 2008 were defined. It was found that a crisis in winemaking in Ukraine has been going on for almost decade with the greatest failure in 2014 that led to the falling overall efficiency. This failure was caused mainly by the military and political factors regarding the annexation of Crimea by Russia, the changes in consumer behaviour with a tendency to reduce overall alcohol consumption, and the government regulation increased excise duties on wines. Despite the efficiency crisis in Ukrainian winemaking, the positive contribution of technological progress provides its productivity growth. The small- and medium-sized enterprises in winemaking have a high resistance to the crisis and fiscal pressure. Despite it losing a half of value-added and being unprofitable, the small wine business has managed to increase the labour and capital productivities and overtake big wine business on these indicators. Research limitations/implications: This study is limited to one country and the relatively small sample of the wineries. However, it can be a starting point for a series of research on the development of anti-crisis winemaking strategy. Practical implications: The findings of the study can be helpful for the Ukrainian Government to prevent crisis continuation in the winemaking sector. This case may be instructive for other countries, faced with a protracted crisis of efficiency in winemaking. Originality/value: This is the first study that examines the winemaking performance and its factors after the world financial crisis, based on the case of Ukraine.